Rewilding, "the Hoop," and Settler Apocalypse - Seraphin, Bruno (The Trumpeter)

(untitled) (Athabasca University Press, 2016)
This paper presents an ethnographic account of a grassroots network of mostly white-identified nomads who travel in the northwest United States’ Great Basin and Columbia Plateau regions. Living mostly on National Forest land, this movement of “rewilders” appropriates local Indigenous peoples’ traditional ecological knowledge in order to gather and replant wild foods in a seasonal round that they refer to as the “Sacred Hoop.” I discuss the Hoop network in order to explore the environmental ethics of a group that is at once strikingly unique and also an embodiment of the problems of settler colonialism within the broader environmentalist movement. I begin by introducing the group's ecologies and ethics, and subsequently move into an examination of the multiple and sometimes-contradictory lines of apocalyptic narrative logic at work in Hoopster discourse. I assert that the Hoopsters’ conflicting accounts of the Anthropocene, and the temporality of its disasters, are a manifestation of their ongoing work grappling with their own racial positionality. Despite the Hoopsters’ uncompromising critiques of colonialism, capitalism, and environmental exploitation, they struggle to come to terms with their role in ongoing colonialism and the marginalization of Indigenous peoples. In this way, the Hoopsters echo the troubled narratives at work in broader North American environmental thought, which consistently reveres the idea of Indigenous cultures while failing to enter into solidarity relationships with contemporary Indigenous communities and their efforts toward decolonization.